Association of dipeptidyl peptidase-4 inhibitor use and the risk of asthma development among type 2 diabetes patients. (November 2022) - Li, Peng-Fei; Chung, Chi-Hsiang; Liu, Jhih-Syuan; Lu, Chieh-Hua; Su, Sheng-Chiang; Kuo, Feng-Chih; Ho, Li-Ju; Chen, Kuan-Chan; Su, Yu-Te; Chu, Nain-Feng; Lee, Chien-Hsing; Hsieh, Chang-Hsun; et al.
Background: Numerous studies have shown that dipeptidyl peptidase-4 inhibitors (DPP-4i) may regulate immunological pathways implicated in asthma. The association between DPP-4i use and risk of asthma development is limited, however. Aim: We aimed to evaluate if DPP-4i treatment in individuals with type 2 diabetes mellitus (T2DM) is associated with a lower risk and severity of asthma. Methods: We performed a population-based retrospective cohort study using the Longitudinal National Health Insurance Research database between 2008 and 2015. After one-to-four propensity score matching from 1, 914, 201 patients with defined criteria, we enrolled 3001 patients who were on DPP-4i (DPP-4i group) for a diagnosis of T2DM but without a diagnosis of asthma for further analysis. Cox proportional hazards regression analysis was performed to estimate and compare the risk of developing and severity of asthma, including no acute exacerbations event (No-AE), acute exacerbations (AEs), status asthmaticus (Status), and required endotracheal intubation (ET-tube intubated), between the two groups. Results: The participants had a mean age of 66.05 ± 17.23 years and the mean follow-up time was 4.96 ± 4.39 years. The risk of asthma development was significantly lower in the DPP-4i group than in the non-DPP-4i group [adjusted hazard ratio (HR) = 0.65; 95% confidence interval (CI) = 0.29–0.83; p < 0.001], with a class effect. This trend was observed for severity of asthma as No-AE (HR = 0.55; 95% CI = 0.24–0.70; p < 0.001), AE (HR = 0.57; 95% CI = 0.26–0.73; p < 0.001), and Status (HR = 0.78; 95% CI = 0.35–0.99; p = 0.047), but not in ET-tube intubated cases (HR = 0.96; 95% CI = 0.43–1.22; p = 0.258). Conclusion: The use of DPP-4i decreased the risk and severity of asthma with a class effect among No-AE, AE, status of asthma events, but not in ET-tube intubated events. Our report suggests that DPP-4i may play a role in attenuating the impact of asthma on incidence in the future and on more severe forms of disease exacerbation in T2DM patients.